A qualitative analysis of eating behaviour change for patients with diabetes and non‐dialysis dependent chronic kidney disease stages 4–5. Issue 4 (23rd October 2018) - Notaras, Stephanie; Conti, Janet
SUMMARY: Background: Dietary changes recommended for chronic kidney disease (CKD) stages 4–5 and concurrent diabetes are difficult to follow given the multitude of food and fluid restrictions aimed at reducing the rate of CKD progression. Reduced adherence is commonplace and there is limited literature on patients' experiences with dietary changes and potential strategies to overcome this. Objectives: Examine patients' experiences when adopting dietary changes recommended for CKD Stages 4–5 (pre‐dialysis) and diabetes, and their perceptions of dietetic services and how they can be improved to assist them with dietary change. Methods: An exploratory qualitative study was undertaken using a purposive sampling method from a dietetic pre‐dialysis clinic. Participants were interviewed using a semi‐structured interview style. Data were analysed using an inductive thematic analysis from a constructivist perspective. Results: Three themes were identified: (1) Negative motivation to change eating behaviour to avoid dialysis; (2) sustaining motivation for change is challenging due to a sense of loss and confusion to incorporate the dietary changes recommended and (3) support is needed for eating behaviour change. Conclusion: These findings have implications for dietitians to enhance their understanding of the patient experience and improve their skills in motivational counselling. Development of dietitian‐specific communication and nutrition counselling programmes are recommended to equip dietitians with skills to better support patients. CKD Stage 3 nutrition education programmes could be beneficial to promote earlier access to dietetic services and dietary recommendations.